COX-2 AND BRCA1 HAVE ALTERED EXPRESSION PROFILE IN DIFFERENT CANINE TUMORS - H. Sadia; S. Manzoor; A. Wajid; M. Tayyab; S. Firyal; A. S. Hashmi; T. Yaqub; Z. U. Mughal; A. K. Mehmood; A. R. Awan; K. Mahmood; M. Y. Khan; et al. (Journal of Animal and Plant Sciences, 2016)
Cancer originates from the unnatural divisions of cells that have constant mutations in the genes which are involved in cell propagation and endurance. Dogs are beloved pet animals and they suffer from many cancers like humans. Mutated BRCA1 and COX-2 abnormal gene expression have been seen in a large number of cancers previously. In this research  gene sequencing and gene expression of COX-2 and BRCA1 genes in 22 different canine tumors and 25 normal canine samples were performed. All samples were collected from Punjab Province, Pakistan. The whole coding region of COX-2, comprised of almost 1812bp with ten exons in dog and the hot spot N (1, 2 and 12 exons) and C- terminal (18, 19, 20, 21 and 22 exons) of BRCA1 gene which include 2024bp were  included in mutational studies. There was no mutation in the coding region of COX-2 and 5’- and -3’ region of BRCA1. The gene expression of COX-2 and BRCA1 in all aforementioned tumors was measured by real time qPCR. BRCA1 high grade negative expression and COX-2 positive gene expression were observed in this study. About 45% tumors showed up-regulation of COX-2 and four tumors showed highest gene expression, two CTVTs, one head tumor and one mammary tumor with fold changes 942.93, 122.79, 85.95 and 44.49 respectively. All granulomas showed down-regulation of COX-2 gene.  It has been observed during this study that the loss of BRCA1 gene expression and up-regulation of the COX-2 gene may have a role in canine tumors.  Altered expression of COX-2 gene in tumors may have link with the extent of aggressive tumor types. The mechanism behind the abnormal function of these genes is not clear yet, however, abnormal expression of COX-2 and BRCA1 in tumors may be associated with the most aggressive and poor prognosis of cancer types and further studies are required.
Keywords: Tumor; Canine transmissible venereal tumors; gene expression; gene sequencing; fold change; mutation